Image of The Jew in “Sleep of the Gazelles” - Nassar, Farid Khalil (Journal of Arabic Language Sciences and Literature, 2023)
Palestine has been, and continues to be, groaning under the weight of intense and bitter conflicts for more than a century. It has witnessed wars, confrontations, losses, and defeats, with the first victims being the Arab Palestinians who lost their land and home. The Palestinian people lie on the open grounds and sleep under the open sky, while most of their children have become displaced and scattered across Arab and non-Arab countries. Consequently, all of this was inevitably reflected in Palestinian literature, both in poetry and prose. This research, through the approach of inductive reasoning, aims to depict the image of the Jew, one of the parties involved in the conflict, as portrayed in the novel "Sleep of the Gazelles" by the Palestinian writer Muhammad Ali Taha. It seeks to unveil the essential characteristics of the Jewish literary persona and their practices. Our selection of this aspect, that is the image of the Jew in the novel "Sleep of the Gazelles", is due to the significance of this relatively new literary work and because this novel/biography covers a period of more than six decades, during which Palestine witnessed numerous significant events. The documentation of these events by the author reinforces the Identity of the Palestinian subject that struggled and continues to fight to remain on their land and in their homeland.